SISTEM PENDAFTARAN BIMBINGAN BELAJAR MENGGUNAKAN METODE PROFILE MATCHING - Evi Dwi Wahyuni; Nur Tahyudin; Maskur Maskur (Universitas Islam Sumatera Utara, 2018)
One form of education that we can get is learning guidance. In conducting learning guidance required process of meeting between teachers and students. Learning guidance enrollment system using profile matching method is a system that can be a media for students with teachers. Profile matching is a method of decision-making system that uses variable data comparison in the form of criteria owned between a part. This system is used to provide teacher recommendations to learners by using a comparison of data in the form of criteria, among others, origin address, address in Malang, hobbies, education history and experience. The Gap value obtained from the criteria data calculated on the Core Factor and Secondary Factor will then be performed N as the total value of the assessment aspect. With variable data comparison on every aspect of the ordering system guidance of learning can provide recommendations to teachers to learners who possess the level of matching data based on the calculations that have been done.